Directly Sequenced Genomes of Contemporary Strains of Syphilis Reveal Recombination-Driven Diversity in Genes Encoding Predicted Surface-Exposed Antigens - Grillová, Linda; Oppelt, Jan; Mikalová, Lenka; Nováková, Markéta; Giacani, Lorenzo; Niesnerová, Anežka; Noda, Angel A.; Mechaly, Ariel E.; Pospíšilová, Petra; Čejková, Darina; Grange, Philippe A.; Dupin, Nicolas; et al. (Frontiers in Microbiology, 2019)
Syphilis, caused by Treponema pallidum subsp. pallidum (TPA), remains an important public health problem with an increasing worldwide prevalence. Despite recent advances in in vitro cultivation, genetic variability of this pathogen during infection is poorly understood. Here we present contemporary and geographically diverse complete treponemal genome sequences isolated directly from patients using a methyl-directed enrichment prior to sequencing. This approach reveals that approximately 50% of the genetic diversity found in TPA is driven by inter- and/or intra-strain recombination events, particularly in strains belonging to one of the defined genetic groups of syphilis treponemes: Nichols-like strains. Recombinant loci were found to encode putative outer-membrane proteins and the recombination variability was almost exclusively found in regions predicted to be at the host-pathogen interface. Genetic recombination has been considered to be a rare event in treponemes, yet our study unexpectedly showed that it occurs at a significant level and may have important impacts in the biology of this pathogen, especially as these events occur primarily in the outer membrane proteins. This study reveals the existence of strains with different repertoires of surface-exposed antigens circulating in the current human population, which should be taken into account during syphilis vaccine development.